INQUIRY DISCOVERY LEARNING METHOD TO IMPROVE STUDENT LEARNING ACHIEVEMENT IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS - Sukawati, Farha; Saude, Saude; Yusra, Yusra; Ubadah, Ubadah (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2023)
This article discusses the use of inquiry discovery learning method to improve students’ learning achievement in Islamic religious education subject at a junior high school in Palu city. This study used a qualitative method with data collection techniques such as direct observation, in-depth interviews, and document analysis. The research findings show that our study conclude that the use of HOTS in learning Islamic religious education can improve students achievement. The students not only increase their achevement in learning the Islamic religious knowledge, but they also have high order thinking skill which support them to think critically regarding various topic in Islamic education subject. They also have skill to collaborate, communicate, and cooperate during learning the subject with their friends.